Designing Liquid-Gas Rate Window of Aerated Drilling Using Guo-Ghalambor Method - Anwar, Fauzia Fadhila; Wardana, Raka Sudira (Jurnal Migasian, 2020)
Loss circulation is a common problem in geothermal drilling due to naturally fractured formation and depleted reservoir pressure. This problem might lead to another problem such as a stuck pipe. In some cases, LCM is not effective in curing loss in a naturally fractured formation and cannot be used to cure loss circulation in the production zone. One of the methods that can be used to prevent loss circulation and also preventing reservoir damage in geothermal drilling is underbalanced drilling or aerated drilling. In an underbalanced or aerated drilling operation, the ratio of air injection rate ad liquid rate is critical to ensure the cutting carrying capacity while preventing hole problems. Usually, computer simulations are used to determine the safe gas-liquid rate limit due to the complexity of the multiphase flow in an underbalanced drilling system. Since the simulation software is not always available, a simpler and reliable method is needed to determine the gas-liquid rate limit in aerated drilling. the purpose of this paper is to design the operating window of the gas-liquid rate ratio in aerated drilling. the purpose of this paper is to design the operating window of gas-liquid rate ratio in aerated drilling using a simple yet reliable method such as the Guo-Ghalambor Liquid-Gas Rate Window method. The result of this research is a gas-liquid rate envelope that can be used to promote good cutting transport, preventing formation and borehole damaged while preventing loss circulation in geothermal well.